Therapeutic Role of Methanolic Extract of Ocimum basilicum L. Seeds and its Isolated Compound as Potent Antidiabetic and Antihyperlipidemic Agents - Parikh, Nisha H.; Kothari, Charmy (Natural Products Journal, The, 2020)
Background: Ocimum basilicum seed, commonly also known as Takhmaria in Gujarat. The seed of O. basilicum traditionally used to treat diabetes. This activity is related to the presence of flavonoids, the major compounds of the crude extract. Objective: The present study was planned to examine the antidiabetic and antihyperlipidemic potential of Ocimum basilicum Linn seed, used as a traditional treatment for diabetes mellitus. Methods: The methanolic extracts of O. basilicum seed (40 mg/kg) and isolated compound apigenin (10 mg/kg) were administered orally for 15 days to streptozotocin (STZ)-induced diabetic rat. Anti diabetic activity, oral glucose tolerance test, change in body weight and lipid profile of diabetics rat treated with methanolic extracts of O. basilicum seed and isolated apigenin were assessed and which was further compared with normal, diabetic control and standard drug-treated rat. Histological examination was carried out on 15 days of treatment. Results: Methanolic extract of O. basilicum seed (40 mg/kg) and apigenin (10 mg/kg) produced a significant reduction in fasting blood glucose level (p<0.01) and (p<0.001) respectively in the streptozotocin-induced diabetic rat. Significant differences were observed in oral glucose tolerance test, serum lipid parameters and body weight for methanolic extract of O. basilicum and apigenintreated diabetic rat as compared to diabetic, normal and standard drug-treated rat. The outcome of the histological examinations of the pancreas treated with a methanolic extract of O. basilicum and apigenin showed comparable regeneration of the cells, which were earlier necrosed by streptozotocin. Methanolic extract of O. basilicum and isolated compound apigenin exhibit significant antihyperglycemic and antihyperlipidemic activities in streptozotocin-induced diabetes in the rat. Conclusion: From above findings, it can be concluded that the O. basilicum seed and isolated compound apigenin must be considered as a potential candidate for the treatment of diabetes and lipidlowering activities in streptozotocin-induced diabetes in the rat.
Keywords: flavonoid